Public Perceptions of Recovery Prospects and Peer Style (Support and Confrontation) in Services for Serious Mental Illness Versus Substance Use Disorder. Issue 4 (2nd October 2019) - Corrigan, Patrick W.; Qin, Sang; Davidson, Larry; Schomerus, Georg; Shuman, Valery; Smelson, David
Abstract: Objective: Peer services have been identified as a key agent in promoting recovery (both as an outcome and as a process) for people with co-occurring disorders. We attempt to make sense of this connection here by examining public perceptions of recovery and peer services separately for serious mental illness (SMI) and substance use disorder. Two different styles may guide peers in providing SMI or substance use disorder services: support or confrontation. The goal of this preliminary study is to examine how styles differ across SMI and substance use disorder conditions and how perceptions of peer style are associated with recovery. Methods: One hundred ninety-five people representing the general public were recruited online via the Amazon MTurk platform. They were asked to complete measures of their endorsement of peer styles and recovery (overall, as-an-outcome, and as-a-process). Results: Peers-as-supportive was endorsed more than confrontational for both SMI and substance use disorder groups. Confrontation was endorsed more for substance use disorder compared to SMI. Overall recovery and recovery-as-process were positively associated with peers-as-supportive for both SMI and substance use disorder. No recovery indices were significantly associated with peers-as-confrontational. Recovery-as-outcome was also associated with peers-as-supportive for substance use disorder. Conclusions: These findings have potential implications for peers and their style in SMI and substance use disorder services as well as in the unique interventions for people with dual disorders.